PENGARUH LAMA FERMENTASI OLEH Bacillus subtilis TERHADAP KARAKTERISTIK SERE KEDELE - Sipayung, Sri Madiarti; Rai Widarta, I Wayan; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPA, 2019)
This research aims to find out the effect of soybean fermentation time by Bacillus subtilis to produce sere kedele with the best characteristics. This research used completely randomized design (CRD) with one treatment factor of the fermentation time with 5 period of fermentation time (12, 18, 24, 30 and 36h). Each treatment was repeated 3 times, resulted 15 experimental units. The data were then analyzed with Analysis of Variance method and if the treatment had an effect on the variable, followed by the Duncan test. The result show that fermentation times had significant effect to moisture, ash, protein, fat, carbohydrate, crude fiber content, total acid, pH value, the number microbes, hedonic test for taste, scoring test for taste and overall acceptance of sere kedele . Fermented by B. subtilis for 12h resulted in the best characteristic under the following criteria : 58.05% moisture content, 2.39% ash content, 15.79% protein content, 14.39% fat contetnt, 9,38% carbohydrate content, 6.1 pH value, 0.11% total acid, 9.59log cfu/g the number microbes, color, flavour, texture liked, normal taste with sour taste and overall acceptance liked.   Keyword : soybean, sere kedele, Bacillus subtilis, fermentation, traditional food .